Analysis of Factors Affecting Auditor Switching on Manufacturing Issuers - Wasito, Wasito; Wardayati, Siti Maria; Wahyu, Nining Ika; Wijaya, Dwi Indriani Fidiastutik; Sari, Dinda Putri Wulan (Proceeding UII-ICABE, 2020)
The study is aimed to analyze management substitution, company size, public accounting firm size, financial distress, and auditor specialization on auditor switching. The sample in this study is a manufacturing companies sited on the IDX. The secondary data used is the financial statements that include the auditor’s report within 2014 to 2017. The sample obtained through purposive sampling method. This research belongs to a quantitative research. The data analysis technique used is logistic regression analysis. The data that was successfully processed showed that the variables of management substitution company size, public accounting firm size, financial distress, and auditor specialization did not support the occurrence of auditor switching. Keywords: Auditor Switching, Management Substitution, Company Size, Financial Distress, Auditor Specialization.